Human monotheism in Allah SWT in the anthology of the rain of june: A hermeneutic study of Paul Ricoeur - Wardana, Reki Kusuma; Wulandari, Yosi (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The Anthology of Poetry in the Book of Rain in June by Sapardi Djoko Damono is a literary work that has various dimensions of interpretation of meaning and can be interpreted in various scientific disciplines. One of them is the science of monotheism. This research aims to analyze monotheism and explain its practice with the characteristics of unification and recognition in the science of monotheism contained in word symbols, phrases or sentences in the book written by Sapardi Djoko Damono entitled June Rain. Using Paul Ricoeur's hermeneutical approach theory to answer the question of human monotheism in Allah SWT, the research was conducted using descriptive qualitative methods and data collection techniques in the form of literature reviews. The research results show that there are two characteristics of the science of monotheism, namely unification and recognition of Almighty Allah. These two characteristics were analyzed in three steps, namely symbols, interpretation and interpretation, which then resulted in 13 poetry titles being analyzed, resulting in 17 symbolic findings in the characteristics of unification and 19 symbols in the characteristics of the recognition of the science of monotheism. After the process of lexical interpretation and interpretation, it was found that the practice of the characteristics of unification in the science of monotheism found in the June Rain Book was found, namely practicing the contents contained in Surah Al-Fatihah. Apart from that, the second characteristic, namely the confession in the analysis of the poem, has the essence of the practice of achieving the knowledge of monotheism, namely carrying out servitude by performing prayers.